Control of responding by location of auditory stimuli: adjacency of sound and response. - Harrison, J M (1977)
Four rhesus monkeys were trained to respond on one key when a one-second noise burst was presented through one speaker and to respond on a second key when the noise burst was presented through a second speaker. The acquisition of stimulus control was studied under three conditions, in each of which the relationship between the sound source and the response-key positions varied: an adjacent condition in which the noise burst was presented through the key and a response on this key was reinforced; a reversed-adjacent condition in which the noise burst was presented through one key and responding on the other key was reinforced: and a nonadiacent condition in which responding on the key nearer the sound was reinforced. Under adjacent conditions, stimulus control developed within one or two sessions. Under reversed and nonadjacent conditions, 10 sessions were required for the development of control. The asymptote of correct responding was the same under each condition in all animals.